The efficacy of “hybrid” percutaneous coronary intervention in chronic total occlusions caused by in-stent restenosis: insights from a US multicenter registry - Christopoulos, Georgios (2014)
OBJECTIVES: To examine the success and complication rates in percutaneous coronary intervention (PCI) for chronic total occlusion (CTO) caused by in-stent restenosis (ISR). BACKGROUND: PCI for in-stent total occlusive disease has traditionally been associated with low success rates. We sought to examine angiographic and procedural outcomes of patients who underwent CTO PCI due to ISR using the novel “hybrid” algorithm, and compare them with patients with de novo CTOs. METHODS: We examined 521 consecutive patients who underwent CTO PCI at 5 high volume PCI centers in the United States using the “hybrid” approach. Clinical, angiographic and procedural outcomes were compared between CTOs due to ISR and de novo CTOs. RESULTS: The target CTO was due to ISR in 57 of 521 patients (10.9%). Compared to patients with de novo CTOs, those with CTO due to ISR had higher frequency of diabetes (56.1% vs. 39.6%, p=0.02) and less calcification (5.3% vs. 16.2%, p<0.001), but longer occlusion length [38 (29-55) vs. 30 (20-51), p=0.04]. Technical success in the ISR and de novo group was 89.4% vs. 92.5% (p=0.43), respectively; procedural success was 86.0% vs. 90.3% (p=0.31), respectively; and the incidence of major adverse cardiac events was 3.5% vs. 2.2% (p=0.63), respectively. CONCLUSIONS: Use of the “hybrid” approach to CTO PCI was associated with similarly high procedural success and similarly low major complication rates in patients with de novo and ISR CTOs.